Study on Effect of Remaining Dentin Thickness and Coronal Pulp Size on Dentin Hypersensitivity Following Tooth Preparation - Ayer, Ashok (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: Dentin hypersensitivity and pain following tooth preparation of vital teeth occurs with a highly variable prevalence often leading to constant pain requiring endodontic therapy. The study was conducted with objective to evaluate the impact of remaining dentin thickness, coronal pulp size, tooth wear on dentin hypersensitivity following tooth preparation. Materials & Methods: Total 138 permanent vital teeth for abutment of fixed partial prosthesis were included in the study. Tooth wear measured using ‘exact tooth wear index’ and level of sensitivity to stimuli was recorded using a numerical rating scale. Following tooth preparation radiograph using paralleling technique were used for measurement of remaining dentin thickness and pulp chamber. Results: The multiple linear regression predictor model summary and overall fit statistics indicated a high degree of correlation (R = 0.661, 0.889, 0.839 for anterior, premolar and molar teeth respectively). The total variation for pain could be explained in 43.7% (anterior), 79.1% (premolar), and 70.4% (molar) by the independent variables and there was a significant linear relationship between the variables in the model (p < .001). Conclusion: This study investigated few possible variables that may be taken into consideration before referring the vital abutment tooth for intentional root canal therapy so that every attempt can be made to avoid pulp amputation.